PEDAGOGICAL CONDITIONS FOR DEVELOPING THE PROFESSIONAL COMPETENCE OF FUTURE TEACHERS (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This article reveals the essence of the concept of competence. Ways of pedagogical development of professional competence in students are indicated. The content of the set of competencies that determine the level of development of pedagogical competence that can be acquired by future teachers is highlighted.